If a,b,c,d are in continued proportion,prove that:
(in the above image)
ii)(a²-b²) (c²-d²)=(b²-c²)²
Attachments:
![](https://hi-static.z-dn.net/files/d25/80223c27154ee560d9419ce3324f0866.jpg)
Answers
Answered by
9
Hope it'd help you..... ..
Attachments:
![](https://hi-static.z-dn.net/files/db1/01bb5ea86fb6a11aba8cd691ec514616.jpg)
Answered by
2
(a² - b²)(c² - d²) = (b² - c²)² Proved.
Step-by-step explanation:
The numbers a, b, c, and d are in continued proportion.
So, (Say)
So, a = kb, b = kc and c = kd
⇒ a = k²c = k³d
and, b = kc = k²d
Then, we have to prove that (a² - b²)(c² - d²) = (b² - c²)²
Now, Left hand side
= (a² - b²)(c² - d²)
= (a + b)(a - b)(c + d)(c - d)
= (k³d + k²d)(k³d - k²d)(kd + d)(kd - d)
=
Now, Right hand side
= (b² - c²)²
= (b + c)²(b - c)²
= (k²d + kd)² (k²d - kd)²
=
Hence, proved that LHS = RHS.
Similar questions
Political Science,
9 months ago
English,
1 year ago
English,
1 year ago
Computer Science,
1 year ago